2005
DOI: 10.1038/sj.eye.6702166
|View full text |Cite
|
Sign up to set email alerts
|

Continuous expression of the homeobox gene Pax6 in the ageing human retina

Abstract: Purpose In the past few years, the essential role of the homeobox gene Pax6 for eye development has been demonstrated unambiguously in a variety of species including humans. In humans, Pax6 mutations lead to a variety of ocular malformations of the anterior and posterior segment. However, little is known about PAX6 expression in the adult human retina. We have therefore investigated PAX6 levels and localization in the human retina at various ages. Methods Adult human eyes of various ages (17-79 years) were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 17 publications
(28 reference statements)
3
34
0
Order By: Relevance
“…We indeed detected Pax6 in the inner nuclear layer of human retina (Fig. 3B, left), in agreement with previous reports (58). However, we did not detect Pax6(S) in retina (Fig.…”
Section: A) Indicating That the Novel S Tail Of Pax6(s) Does Not Chsupporting
confidence: 93%
“…We indeed detected Pax6 in the inner nuclear layer of human retina (Fig. 3B, left), in agreement with previous reports (58). However, we did not detect Pax6(S) in retina (Fig.…”
Section: A) Indicating That the Novel S Tail Of Pax6(s) Does Not Chsupporting
confidence: 93%
“…Expected sizes for PAX6 proteins are 46 kDa (canonical PAX6) and 48 kDa (PAX6(5a) and 3ϫFLAG-PAX6). Retinal tissues express both forms of PAX6 and are a size control for both isoforms (45). B, reverse transcription-PCR analysis for the expression of PAX6 and PAX6(5a) transcripts in MIAPACA-2 (lanes 1 and 2) and PANC-1 (lanes 3 and 4).…”
Section: Electrophoretic Mobility Shift Assay (Emsa)-whole Cell Extramentioning
confidence: 99%
“…27 Although PAX6 was extensively studied during eye organogenesis in various species, little is known about PAX6 expression and function in adult eye tissues. PAX6 expression in the GCL and INL of the inner retina was observed in humans, 23 chicken, 28 and mouse 29 and Zhang et al 30 detected PAX6 expression in the adult lens epithelium. Bcl-2 indicates B-cell leukemia/lymphoma-2; Bcl-X L , B-cell leukemia/ lymphoma extra long; GFAP, glial fibrillary acidic protein; IL-1b, interleukin-1b; TIMP-1, tissue inhibitor of metalloproteinase-1; XIAP, X-linked inhibitor of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…De Melo et al 22 showed that several homeobox genes including Pax6 are expressed in the young adult mouse retina and we recently reported continuous expression of PAX6 in the young, adult, and old normal human retina. 23 To investigate the role of PAX6 expression in the adult eye and to assess whether PAX6 is involved in degenerative processes of the retina, we studied PAX6 expression in wild type and in calcitonin receptor-like receptor transgenic (CLR SMaA ) mice with acute angle-closure glaucoma (ACG). 24 …”
Section: Pax6 Expression and Retinal Cell Death In A Transgenicmentioning
confidence: 99%